A Review On Pyrimidine Derivatives As A Potential Anticancer Agents - Ashish Dhanwate; Priya Kotkar; Abhijit Hon; Prof Preetam L.Nikam; Dr Dipti G.Phadtare; Shreyash Ahire; Hariom Malpani; Aniket Tripathi (Revista Electronica de Veterinaria, 2025)
Cancer affects people's quality of life, poses a threat to world health, and has a number of negative side effects when treated. The search for new anticancer agents has been prompted by the resistance of cancer cells to the available medications. A favored scaffold called pyrimidine is found in living things and is essential for many biological processes, including the development of cancer. It is regarded as an important molecule in the therapy of cancer because of its structural similarities to the nucleotide base pair of DNA and RNA.In the past several years, a large number of brand-new pyrimidine derivatives have been created and studied for their anticancer activities. Focusing on the structure-activity relationship (SAR) of pyrimidine derivatives as an anticancer agent throughout the past ten years is the main goal of the current review.This review aims to aid in the creation of pyrimidine-based anticancer medications that are stronger and more effective.